2012
DOI: 10.1097/pgp.0b013e318220ba16
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of NOL7 Gene Point Mutations, Promoter Methylation, and Protein Expression in Cervical Cancer

Abstract: NOL7 is a putative tumor suppressor gene (TSG) localized to 6p23, a region with frequent loss of heterozygosity (LOH) in a number of cancers, including cervical cancer (CC). We have previously demonstrated that reintroduction of NOL7 into CC cells alters the angiogenic phenotype and suppressed tumor growth in vivo by 95%. Therefore, to understand its mechanism of inactivation in CC, we investigated the genetic and epigenetic regulation of NOL7. NOL7 mRNA and protein levels were assessed in thirteen CC cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Increased amounts of SRPK2 can lead to the hyperphosphorylation of serine-arginine-rich proteins, which in turn induces changes in alternative pre-mRNA splicing observed in PD [ 34 ]. NOL7 is a candidate cancer suppressor that localizes to 6p23, a segment with frequent loss of heterozygosity (LOH) in many tumors [ 61 ]. NOL7 interacts with amyloid precursor protein (APP) protein which accumulates in mitochondrial membrane in PD, and that APP interacts with LRRK2 and then is phosphorylated at Thr668 within its intracellular domain to promote neurotoxicity in PD [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased amounts of SRPK2 can lead to the hyperphosphorylation of serine-arginine-rich proteins, which in turn induces changes in alternative pre-mRNA splicing observed in PD [ 34 ]. NOL7 is a candidate cancer suppressor that localizes to 6p23, a segment with frequent loss of heterozygosity (LOH) in many tumors [ 61 ]. NOL7 interacts with amyloid precursor protein (APP) protein which accumulates in mitochondrial membrane in PD, and that APP interacts with LRRK2 and then is phosphorylated at Thr668 within its intracellular domain to promote neurotoxicity in PD [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous researchers have confirmed that consistent loss of NOL7 through loss of heterozygosity and decreased mRNA and protein expression has been observed in cervical cancer [ 7 ]. Additionally, the experimental study performed by Lingen MW et al also confirmed the suppressive function of NOL7 in cervical cancer [ 7 ].…”
Section: Discussionmentioning
confidence: 54%
“…Previous researchers have confirmed that consistent loss of NOL7 through loss of heterozygosity and decreased mRNA and protein expression has been observed in cervical cancer [ 7 ]. Additionally, the experimental study performed by Lingen MW et al also confirmed the suppressive function of NOL7 in cervical cancer [ 7 ]. However, the chromosome region 6p21–23, where NOL7 resides, is frequently amplified in several cancers, including melanoma, and therefore may exert disease-promoting effects in these cancers [ 12 ].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…To determine the compartment in which NOL7 must reside for its function, we made a series of mutational constructs that targeted NOL7 to the nucleolus (NOL7 wild-type), nucleoplasm (N23(−)) or cytoplasm (N123(−)) (Zhou et al 61 ; Figure 1a). In SiHa cells, which essentially lack endogenous NOL7, 60,62 reintroduction of wild-type nucleolar NOL7 was able to significantly upregulate endogenous TSP-1 expression compared with GFP controls, while cytoplasmic NOL7 had no effect on TSP-1 levels (Figure 1b). However, nucleoplasmic NOL7 was still able to upregulate endogenous TSP-1 to the same levels as wild-type nOl7 (Figure 1b).…”
Section: Resultsmentioning
confidence: 97%